Prognostic score in patients with recurrent or metastatic carcinoma of the head and neck treated with cetuximab and chemotherapy - Magnes, Teresa (PLoS One, 2017)
Despite modern treatment approaches, survival of patients with recurrent or metastatic squamous cell carcinoma of the head and neck (SCCHN) remains low and it is difficult to identify patients who derive optimal benefit from treatment. We therefore analyzed which commonly available laboratory and clinical parameters may help improve the prognostication in this patient group. This retrospective monocenter analysis includes 128 patients with recurrent or metastatic SCCHN treated with cetuximab alone or in combination with polychemotherapy as first line therapy. Factors with independent prognostic power in the multivariate analysis were used to build up a score separating patient groups with different survival. Patients had a median age of 61 years and 103 patients were treated with polychemotherapy plus cetuximab. An ECOG score above 1, high CRP and leukocyte levels, less intensive treatment and a time below 12 months from primary diagnosis to relapse remained as independent negative prognostic factors in multivariate analysis. Patients with 0 to 1 risk factors had a median OS of 13.6 months compared to a median OS of less than one month for patients 4 to 5 risk factors (p<0.001). This study identifies 5 clinical and serum values that influence survival of patients with recurrent or metastatic SCCHN treated with cetuximab. By combining these factors to create a score for OS, it is possible to distinguish a group of patients with significantly improved survival and define those most likely to have no benefit from cetuximab treatment.